Epidemiological and clinical characteristics of people with venous ulcers attended at municipal health units (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objectives: To describe the sociodemographic and health data of individuals with venous ulcers treated at health services in Ribeirão Preto (São Paulo, Brazil) and to identify aspects of lower limbs and lesions and therapies used in treatment. Method: Quantitative descriptive study developed through the review of medical records, interview with users and evaluation of lower limbs. The data collection was done in the period of four months after the approval of the Institutional Committee of Ethics in Research. Results: 53 individuals with active or healed venous ulcer participated in the study. There was a predominance of individuals older than 60 years(73.5%), women (64.2%) and chronic diseases (73.6%), especially systemic arterial hypertension. Thirty-seven (69.8%) individuals had 72 active ulcers and 16 (30.2%) had 23 healed ulcers. Ulcers were in the lower third of the leg (97.2%), in an area < 49 cm2 (80.6%), with predominance of devitalized tissue (61.1%). Several treatment options were used to protect the wound bed, debridement or absorption of the exudate. Conclusion: The study enabled possible to identify the profile of users with venous ulcer and the assistance provided to them.